If NICE was in the USA - Kendall, T; McGoey, L; Jackson, E (2009)
Decisions about drugs by doctors, patients, and the public depend on a complex framework of industry regulation, professional and public guidance, and transparent publication of the research on which the regulatory framework depends. In the UK, there are two agencies with a national role in this decision-making process. First, a regulator, the Medicines and Healthcare products Regulatory Agency (MHRA), which is akin to the Food and Drug Administration (FDA) in the USA and has statutory responsib ...